The Cell Regulation Mechanism of Neurovascular Unit - Jia, Yuan-Yuan; Chang, Rui-Bi; Yan, Han-Wen; Dai, Rong (International Journal of Biotechnology for Wellness Industries, 2016)
Ischemic cerebrovascular disease is one of the three deadly diseases. It is characterised by high mortality and high morbidity. Because of no effective treatments of recombinant tissue plasminogen activator (rt-PA) and neuroprotectant, there are more and more research focus on neurovascular unit (NVU), which is composed of brain microvascular endothelial cells (BMECs), neuron, astrocyte(AS) and so on. Cell–cell signaling and coupling between these different compartments form the basis for normal function and repair of brain injury. In this mini-review, we will describe the relationship of CMECs, neuron and AS.